2004
DOI: 10.1161/01.res.0000137875.42385.8e
|View full text |Cite
|
Sign up to set email alerts
|

Examining Intracellular Organelle Function Using Fluorescent Probes

Abstract: Abstract-Fluorescence microscopy imaging has become one of the most useful techniques to assess the activity of individual cells, subcellular trafficking of signals to and between organelles, and to appreciate how organelle function is regulated. The past 2 decades have seen a tremendous advance in the rational design and development in the nature and selectivity of probes to serve as reporters of the intracellular environment in live cells. These probes range from small organic fluorescent molecules to fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 105 publications
1
44
0
Order By: Relevance
“…There is a general consensus that iNOS is transiently expressed in the heart during immune responses under stress (8) and, therefore, during pathophysiological conditions of the myocardium such as in ischemia-reperfusion injury (133), septicemia (125), heart failure (146), as well as during aging (138). During the last fifteen years, different groups have used various experimental approaches and reported the presence of mtNOS in the heart (1,10,16,40,45,60,66,72,79,91,115,129,130,140,141,143,147). Regarding the localization of mtNOS, one interesting study provided evidence about the docking of eNOS to the outer mitochondrial membrane in endothelial cells (52).…”
Section: Heart Nossmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a general consensus that iNOS is transiently expressed in the heart during immune responses under stress (8) and, therefore, during pathophysiological conditions of the myocardium such as in ischemia-reperfusion injury (133), septicemia (125), heart failure (146), as well as during aging (138). During the last fifteen years, different groups have used various experimental approaches and reported the presence of mtNOS in the heart (1,10,16,40,45,60,66,72,79,91,115,129,130,140,141,143,147). Regarding the localization of mtNOS, one interesting study provided evidence about the docking of eNOS to the outer mitochondrial membrane in endothelial cells (52).…”
Section: Heart Nossmentioning
confidence: 99%
“…2C). Studies of cardiac mtNOS have used various methods including immunohistochemistry (10,66), spectrophotometry (16,30,45,79,115,141,142), radiometry (139,143), fluorometry (40,139,143,147), chemiluminescence (143), and electrochemistry (72). On the other hand, one study reported that the ubiquinone/cyt bc 1 is a site where nitrite is reduced to form NO congeners within mitochondria in a NOS-independent manner (100).…”
Section: Heart Nossmentioning
confidence: 99%
See 1 more Smart Citation
“…We labeled human BM-MSC with CFSE, which irreversible stains the plasma membrane [203,204], or DiD, which labels all cell membranes, membrane-derived vesicles, and intracellular organelles such as mitochondria [205][206][207]. Consequently, pre-immune fetal sheep were IP injected with either CSFE-positive MSC alone or CFSE-positive MSC in combination with DiD-positive MSC.…”
Section: Results Obtained In Fetal Sheep Modelmentioning
confidence: 99%
“…However, quantitative analysis by this method is labor intensive and is more suitable for experiments using immortalized or primary cell lines. The study of individual mitochondria derived from tissue is significantly more difficult and most methods do not allow for easy identification of mitochondrial subsets concurrently with the evaluation of mitochondrial function 3 .…”
Section: Introductionmentioning
confidence: 99%